Hak Kewarganegaraan dan Tanggung Jawab Negara dalam Menjamin Perlindungan Konsumen - Malik Abdul Aziz; Rida Kusuma Devi; Anis Badriyatun Niswah (International Forum of Researchers and Lecturers, 2025)
Citizenship rights are a fundamental foundation for ensuring the fulfillment of basic rights, including the right to consumer protection. In the context of globalization and the development of the digital economy, the potential for violations of consumer rights is increasing, thereby requiring the state to strengthen its responsibilities. This study aims to analyze the relationship between citizenship rights and the state’s obligations in guaranteeing consumer protection from the perspective of positive law and policy practices in Indonesia. The research method employed is a normative approach with juridical analysis of legislation, court decisions, and legal doctrines, complemented by a comparative study of international regulations. The findings reveal that consumer protection cannot be separated from the state’s recognition of universal citizenship rights. The state plays a role as regulator, facilitator, and supervisor to ensure the fulfillment of consumer rights to safety, comfort, and fairness in transactions. However, gaps were identified between legal norms and implementation, particularly in digital market oversight and the protection of vulnerable consumers. The study concludes that consumer protection is a concrete manifestation of the state’s responsibility for citizenship rights, requiring regulatory strengthening, effective supervisory institutions, and synergy among the state, business actors, and society.